Assembly and Activity of the WASH Molecular Machine: Distinctive Features at the Crossroads of the Actin and Microtubule Cytoskeletons - Fokin, Artem I.; Gautreau, Alexis M. (Frontiers in Cell and Developmental Biology, 2021)
The Arp2/3 complex generates branched actin networks at different locations of the cell. The WASH and WAVE Nucleation Promoting Factors (NPFs) activate the Arp2/3 complex at the surface of endosomes or at the cell cortex, respectively. In this review, we will discuss how these two NPFs are controlled within distinct, yet related, multiprotein complexes. These complexes are not spontaneously assembled around WASH and WAVE, but require cellular assembly factors. The centrosome, which nucleates microtubules and branched actin, appears to be a privileged site for WASH complex assembly. The actin and microtubule cytoskeletons are both responsible for endosome shape and membrane remodeling. Motors, such as dynein, pull endosomes and extend membrane tubules along microtubule tracks, whereas branched actin pushes onto the endosomal membrane. It was recently uncovered that WASH assembles a super complex with dynactin, the major dynein activator, where the Capping Protein (CP) is exchanged from dynactin to the WASH complex. This CP swap initiates the first actin filament that primes the autocatalytic nucleation of branched actin at the surface of endosomes. Possible coordination between pushing and pulling forces in the remodeling of endosomal membranes is discussed.